Interrelationship of Wages Under Joint Demand: The Case of the Fall River Textile Workers - Segal, Martin (Quarterly Journal of Economics, 1956)
I. Introduction, 464. — II. The Fall River case, 466; labor organizations in Fall River, 466; collective bargaining in Fall River, 467. — III. Interrelationship of wages in Fall River, 470.